PERAN KEPUASAN KERJA SEBAGAI MEDIATOR TERHADAP FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA ASN BAPPEDALITBANG KABUPATEN PASER - Irma Yusnita; Amir Fikri; Mieta Istiandra (Journal Publicuho, 2023)
This study aims to determine the Role Of Job Satisfaction As A Mediator On The Factors Affecting The Performance Of The State Civil Apparatus Bappedalitbang, Paser District. This study uses a quantitative method with a correlational approach, namely research that seeks to explain the relationship between the independent variable and the dependent variable through the role of the mediating variable. Furthermore, the data were analyzed using the Structural Equation Modeling (SEM) equation model with the Partial Least Square (PLS) analysis technique with the stages of measurement model analysis and structural model analysis. From the results of the study it can be concluded that there is a positive and significant effect of motivation on performance both without and with job satisfaction as a mediating variable, there is a positive and significant influence on performance both without and with job satisfaction as a mediating variable, there is a positive but not significant influence of leadership on performance both without and with job satisfaction as a mediating variable, there is a positive but not significant effect of work discipline on performance both without and with job satisfaction as a mediating variable, there is a positive and significant effect between job satisfaction as a mediating variable on performance, there is a simultaneous influence of motivation , ability, leadership and work discipline on performance.